Potential of Market Vegetable Waste as Animal Feed in Greater Malang - Badat Muwakhid; Umi Kalsum; Farid Wajdi (UNIVERSITAS ISLAM LAMONGAN, 2023)
This study aims to determine the potential of vegetable waste as animal feed from various traditional markets in the city of Malang. This research is descriptive and experimental. The descriptive method is used to overview the diversity, the amount of availability of various vegetable waste for each season, the type of vegetable waste that dominates the market that is suitable for livestock consumption, and the nutritional value of vegetable waste. The experimental research method used a randomized block design ANOVA with an accuracy of 1% to determine the chemical quality of vegetable waste that dominates several markets and the chemical quality of vegetable waste based on shelf life with observations of 0, 2, 4, and 6 days of storage. The results showed that the accumulation of vegetable waste per day in the selected market was 3774.76 kg in dry matter, equivalent to meeting the consumption needs of 308.14 ruminant units. The conclusion is that the nutritional value of vegetable waste from the market is the same as the nutritional value of elephant grass from DM, OM, CP, DMD, and OMD. Vegetable waste from the market easily loses its nutritional value as a result of the decay process.